Robust Direct Yaw Moment For Optimal Control Using PSO In Step Steering Manoeuvre - Ab Aziz, Ab Wafi; Ghazali, Rozaimi; Chong, Chee Soon; Saadon, Intan Mastura; Omar, Mohd Firdaus; Aripin, Muhamad Khairi (IAEME Publication, 2018)
Direct yaw moment is one of the active safety and handling system, which is used to improve the vehicle stability and steerability by controlling each individual wheel for optimum traction especially in lateral and yaw dynamics. This type of system has been attracting many researchers to introducing a new control strategy for improving the existing system, where one of the prominent linear control strategies is an optimal control theory. By introducing the integral term in the Linear Quadratic Regulator, the offset of the control system can be eliminated which simultaneously enhance the robustness of the system parameters against the external disturbance, un-modelled dynamics or measurement.With the integration of the meta-heuristic computational tuning method, which is known as Particle Swarm Optimization algorithm, the parameters of the Linear Quadratic Integral controller are tuned properly which consequently increase the tracking performance in the step steering simulation test.